Transformação Digital dos Procedimentos de Matrícula do Sistema de Seleção Unificada – Sisu em uma Universidade Federal - Lacerda, Anita Oliveira (2021)
Introduction: The Unified Selection System (SiSU) is the computerized system of the Ministry of Education (MEC) used by several Brazilian Public Institutions of Higher Education to offer places in their undergraduate courses. Since 2017, the Federal University of Espírito Santo (Ufes) has adopted SiSU as the main means of access to its on-site undergraduate courses and offers more than two thousand places at each edition. The selection is carried out through the marks obtained in the National Secondary Education Examination (ENEM) and, after classification of the approved candidates, Ufes calls those approved to attend in person and carry out enrollment procedures. Context: With the pandemic of the new Coronavirus COVID 19, decreed by the World Health Organization in March 2020, and the suspension of on-site activities at the Federal University of Espírito Santo from March 17, 2020, there was an impediment to carrying out the procedures registration of those approved in SiSU Ufes 2020/2. Then, the on-site procedures were converted into remote enrollment procedures, in order to continue SiSU, complying with the schedule established by the Ministry of Education. The problem that presented itself in this work was how to guarantee the enrollment of candidates approved in SiSU Ufes 2020/2 through digital procedures adopted during the Covid 19 pandemic, obeying the principles of transparency and efficiency in Public Administration. Related to this problem is the work performed by various committees to verify the right to quotas, carried out in person in previous editions of SiSU. The main objective was to analyze the perception of the employees involved in relation to the digital registration procedures adopted at the Federal University of Espírito Santo. As for the methods and procedures, the qualitative approach was used, configuring the research as phenomenological. Data collection was carried out through a bibliographic and documental survey, associated with the application of the narrative interview. As aresult, it was observed that the adverse context of suspension of in-person activities and the threat of contamination by the potentially lethal virus COVID 19 was a driving force for the occurrence of a digital transformation that brought improvements to those involved in the enrollment procedures. At the end of this study, it was obtained, as a Technical/Technological Product, a preliminary project to carry out digital registration procedures, with the mapping of the points to be improved.